1992
DOI: 10.4141/cjas92-010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion on ruminal and intestinal disappearance of amino acids in white lupin seed

Abstract: Cros, P., Moncoulon, R., Bayourthe, C. and Vernay, M. 1992

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…Due to the reduction in ruminal degradability, expander treatment increased the calculated intestinal digestibility of undegraded protein and amino acids (data not shown), and similar results have previously been found in a number of studies (Cros et al, 1992;Prestløkken, 1992Prestløkken, , 1999bBenchaar et al, 1993).…”
Section: Total and Intestinal Digestibilitysupporting
confidence: 87%
“…Due to the reduction in ruminal degradability, expander treatment increased the calculated intestinal digestibility of undegraded protein and amino acids (data not shown), and similar results have previously been found in a number of studies (Cros et al, 1992;Prestløkken, 1992Prestløkken, , 1999bBenchaar et al, 1993).…”
Section: Total and Intestinal Digestibilitysupporting
confidence: 87%
“…Moreover, heating CA at 110°C for 2 h reduces CP degradability (Macleod 1987), but this would be a much more severe heat treatment than extrusion. However, extrusion decreases CP degradabiliy of lupins (Cros et al 1992;Kibelolaud et al 1993), which could suggest that the response to extrusion depends on the seed variety or that heat treatment required to effectively decrease CP degradability is not the same for all seeds as previously reported for cereals (Arieli et al 1995).…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, extrusion has the potential of reducing CP degradability as shown in lupin seeds (Cros et al 1992), which could improve the nutritive value of seed as a source of undegraded protein. Khorasani et al (1992) suggested that reducing degradability of the protein-rich matrix surrounding the fat droplets of CA could overcome the negative effects of supplemental fat on ruminal digestion (Devendra and Lewis 1974).…”
Section: Mots Clésmentioning
confidence: 99%
“…To our knowledge, for vetch and bitter vetch, the information available is limited to acid detergent soluble nitrogen values (Aguilera et al., 1992). For lupin (Cros et al., 1992a; Goelema et al., 1998; Solanas et al., 2005) and beans (Cros et al., 1992b; Goelema et al., 1998), high values for IDRUP (from 0.83 to 0.96) and higher than 0.95 for IDDP have been reported using the mobile bag technique in cows.…”
Section: Discussionmentioning
confidence: 99%